Chemical composition and biological activity of lemongrass volatile oil and n-Hexane extract: GC/MS analysis, in vitro and molecular modelling studies - Shaza H. Aly; Abdullahi Ibrahim Uba; Nilofar Nilofar; Taghreed A. Majrashi; Mahmoud A. El Hassab; Wagdy M. Eldehna; Gokhan Zengin; Omayma A. Eldahshan (PLoS ONE, 2025)
Lemon grass, formally identified as Cymbopogon citratus, is a plant that belongs to the Poaceae family. The present work aimed to examine the chemical composition by GC/MS analysis and assess the biological potential of C. citratus volatile oil and n-hexane extract. The volatile oil and n-hexane extract were evaluated for antioxidant potential and tested for their enzyme inhibition against tyrosinase, butyrylcholinesterase (BChE), acetylcholinesterase (AChE), α-amylase, and α-glucosidase. The chemical analysis of the lemongrass n-hexane extract (HE) and volatile oil (VO) revealed that the main constituents in the HE are aliphatic hydrocarbons (42.98%), triterpenoids (20.14%), and aromatic hydrocarbons (17.25%). Conversely, the main constituents of the (VO) are predominantly monoterpenes, namely α-citral (36.08%), β-citral (34.22%), and β-myrcene (13.84%). The oil showed more potent antioxidant potential in DPPH, ABTS, CUPRAC, FRAP, and phosphomolybdenum (10.18, 35.69 mg Trolox equivalent/g, 98.97 and 69.73 mg Trolox equivalent/g and 43.01 mmol Trolox equivalent/g). The HE displayed higher BChE (1.53 mg Galanthamine equivalent)/g), as well as α-amylase and α-glucosidase inhibitory activities (0.39 and 2.40 mmol Acarbose equivalent/g). The VO demonstrated more potent tyrosinase inhibitory activities (57.19 mg Kojic acid equivalent/g) along with acetyl and butyrylcholinesterase inhibition. Dominant compounds exhibited the ability to bind with high affinity to various target proteins, with a particular affinity for AChE and BChE. The volatile oil and n-hexane extract of C. citratus show significant promise as a viable choice for the advancement of novel therapeutic strategies aimed at addressing oxidative stress, neurodegeneration, and diabetes.